EPIDEMIOLOGY OF DIABETIC KIDNEY DISEASE, RISKS, DIAGNOSIS, AND MANAGEMENT. - Magbol Yahia Yahia Arishi; Mishaan Mohamed Ahmed Aljhani; Mohammed Abdu Ammash Khobrany; Hazib Hassan Darraj; Naif Mohammed Ahmed Al Johani; Waleed Yahia Arishi; Mohammed Ali A Mojamammi; Ahmed Mohammed Ahmed Shtefi; Mohammed Mossa Rajeh Darraj; Naif Mohammed Jaber Kalufah; Mohammed Ali Majari; Fatimah Mohammed Naseeb; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Diabetes is widely recognized as the primary etiology behind the development of chronic kidney disease (CKD) and end-stage kidney disease (ESKD) worldwide. Both type 1 and type 2 diabetic individuals commonly manifest CKD, which is characterized by a history of reduced glomerular filtration rate (GFR) and increased albumin excretion in the urine lasting for a minimum of three months. The prevalence of diabetes in the United States has experienced a notable increase from 6 to 10 percent within the past two decades, while the proportion of diabetic patients with concomitant CKD has remained constant. Diabetic nephropathy and chronic kidney disease (CKD) exhibit a higher prevalence among female individuals, African Americans, and individuals of Latino descent. The presence of obesity is acknowledged as a pivotal risk factor for type 2 diabetes and frequently coexists with type 1 diabetes. The most prevalent clinical manifestation is the persistent elevation of albuminuria levels and sustained reduced estimated glomerular filtration rate (eGFR). Most patients with this condition remain asymptomatic, thus necessitating regular and routine checkups for detection. In cases where non-diabetic kidney disease is suspected, a kidney biopsy should be performed. Management of diabetic kidney disease encompasses general approaches involving blood pressure regulation, glycemic control, and lifestyle modifications. In instances of severe albuminuria, angiotensin inhibition represents the preferred pharmacological intervention. This paper will comprehensively examine diabetic kidney disease (DKA), or diabetic nephropathy.